2009
DOI: 10.1063/1.3087515
|View full text |Cite
|
Sign up to set email alerts
|

Strain relaxation in AlGaN multilayer structures by inclined dislocations

Abstract: To examine further the strain relaxation produced by inclined threading dislocations in AlGaN, a heterostructure with three AlGaN layers having successively increasing Ga contents and compressive strains was grown on an AlN template layer by metalorganic vapor-phase epitaxy. The strain state of the layers was determined by x-ray diffraction (XRD) and the dislocation microstructure was characterized with transmission electron microscopy (TEM). As the GaN mole fraction of the heterostructure increased from 0.15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(98 citation statements)
references
References 35 publications
6
86
3
Order By: Relevance
“…Therefore, the highly strained NCI-AlGaN film grown on bulk AlN is expected to contain a significantly lower dislocation density than similar fully relaxed films grown on c-plane sapphire or templates consisting of thin III-Nitride layers grown on c-plane sapphire. It should be noted that other groups have reported on strain relaxation in high AlN mole fraction films (>60%) grown on sapphire or SiC substrates through the formation of dislocations [11,12] in contrast to what we observe for growth of these films on bulk AlN. Understanding this result in terms of the differences in the strain relaxation mechanisms between the AlGaN/ bulk AlN system and the more commonly investigated AlGaN/AlN/c-plane sapphire system requires further investigation.…”
Section: Resultscontrasting
confidence: 46%
“…Therefore, the highly strained NCI-AlGaN film grown on bulk AlN is expected to contain a significantly lower dislocation density than similar fully relaxed films grown on c-plane sapphire or templates consisting of thin III-Nitride layers grown on c-plane sapphire. It should be noted that other groups have reported on strain relaxation in high AlN mole fraction films (>60%) grown on sapphire or SiC substrates through the formation of dislocations [11,12] in contrast to what we observe for growth of these films on bulk AlN. Understanding this result in terms of the differences in the strain relaxation mechanisms between the AlGaN/ bulk AlN system and the more commonly investigated AlGaN/AlN/c-plane sapphire system requires further investigation.…”
Section: Resultscontrasting
confidence: 46%
“…23,32,33 TEM studies done by Cantu et al reported a TDD of $3 Â 10 10 cm À2 , where the TD was inclined by 10 -25 in the 1 100 direction and had a misfit component, thus relieving misfit strain. Observations of Follstaedt et al for compressively strained AlGaN indicated that the TD inclination occurred prior to the introduction of Si, where the average inclination angle was $19 , and the TDD is $6.9 Â 10 9 cm À2 .…”
Section: Theoretical Model and Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19] As mentioned in Ref. 18, Burgers vector analysis is required to prove this.…”
Section: Introductionmentioning
confidence: 99%